An Exploring Experiential-Based Learning in Developing English Speaking Skills: A Qualitative Study of English Student Interns in Food and Beverage: A Qualitative Study - Rahmat Hidayat; Moh Mahmud; Dewi Khawa (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2026)
This study explored the role of Experiential-Based Learning (EBL) in developing English-speaking skills among English Education student interns in the Food and Beverage Department at Bobby’s G-Land Surf Camp. The study focused on three aspects: the types of experiential learning experiences encountered during the internship program, interns’ perceptions of the role of EBL in improving speaking skills, and the challenges and opportunities experienced during the learning process. This research employed a qualitative case study design involving two English Education student interns. Data were collected through observation, semi-structured interviews, and documentation and analyzed using Miles, Huberman, and Saldaña’s interactive model consisting of data condensation, data display, and conclusion drawing. The findings revealed that the interns experienced experiential learning through direct interaction with international guests, workplace communication, reflective learning practices, and the application of communication strategies in authentic workplace situations. The participants perceived EBL as an effective approach for improving speaking fluency, vocabulary mastery, self-confidence, and communicative competence. Furthermore, the interns encountered challenges such as understanding various English accents, limited vocabulary, speaking anxiety, and spontaneous communication demands. However, these challenges also provided valuable learning opportunities that enhanced communication strategies and professional readiness. The findings support Kolb’s Experiential Learning Theory, emphasizing learning through concrete experience, reflective observation, abstract conceptualization, and active experimentation.